Interactive Mental Health and Cognitive Enhancement Platform - Ifrah Ahmed Khan; Mohib Un Nabi, (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2025)
The "Interactive Mental Health and Cognitive Enhancement Platform with Self-Guided Workshop Content" is a web-based application designed to support mental health awareness, cognitive enhancement, and stress management. The platform provides interactive modules, including self-guided workshops, engaging activities, cognitive tests, and therapeutic exercises, all structured in a self-paced format. The platform is built using HTML, CSS, JavaScript, Bootstrap, and Supabase, with deployment on Netlify for accessibility. Loosely based on David Gardner's Theory of Multiple Intelligences, this project aims to cater to diverse learning and cognitive styles. Users can engage in structured workshops, participate in brain-stimulating exercises, and track their mental well-being through assessments. Despite the growing awareness of mental health, accessible and structured digital solutions remain limited. Many existing platforms either lack interactive engagement or fail to provide personalized self-guided learning experiences. Moreover, traditional approaches to mental health and cognitive enhancement do not always cater to diverse learning preferences, as emphasized in Gardner's Theory of Multiple Intelligences. This project addresses these gaps by developing an intuitive, interactive, and self-guided platform that integrates cognitive exercises, therapeutic activities, and mental health awareness, empowering users to manage their mental well-being at their own pace